Tossing the Red Flag: Official (Judicial) Review and Shareholder-Fan Activism in the Context of Publicly Traded Sports Teams - Zachary A. Greenberg (Washington University Law Review, 2013)
For some, it comes after their team squanders away a fourth quarter lead in the playoffs, engages in a hasty trade, or makes an ill-advised substitution. For others, an indefensible draft choice, announcement of team relocation, or decision not to re-sign a star player triggers the thought. Whether at a sports bar or on their own living room couch, at one time or another, every sports fan has transported him or herself to the owner’s box and imagined, “If I ran that team, things would be different.” In the face of numerous professional sports team bankruptcies and league lockouts in the last fifteen years, as well as the current economic client, all professional franchises should be reevaluating their ownership structures and investigating new sources of revenue. Although the notion of a publicly owned and traded sports team is not a new business revelation, current economic conditions have reactivated largely dormant discussions of the opportunity. While the decisions posed throughout this analysis are ultimately left to current sports team ownership, this Note is meant to serve as a thought experiment to provoke questions and to spark discussion regarding the viability of a public model of sports team ownership.
Keywords: sports; shareholders; ownership